2010
DOI: 10.28945/1317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Online Learning Behaviors in School vs. at Home in Terms of Age and Gender Based on Log File Analysis

Abstract: The research objectives of this study are: (a) to compare learning behaviors in an online science learning environment -in school vs. at home; and (b) to explore the existence of some behavioral differences, in school and at home, in terms of age and gender. The actions of 1,179 elementary school students in an online science learning environment were documented in a log file and statistically analyzed. Results suggest that students who learn at home tend to spend more time learning; they learn at a slower pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…However, the analysis showed no significant difference in their online behaviors in term of gender. This result is in line with the study Ben-Zadok and her colleagues conducted on elementary schools in Israel (Ben-Zadok, Leiba, & Nachmias.,2010).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the analysis showed no significant difference in their online behaviors in term of gender. This result is in line with the study Ben-Zadok and her colleagues conducted on elementary schools in Israel (Ben-Zadok, Leiba, & Nachmias.,2010).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Ben-Zadok, Leiba and Nachmias (2010) compared learning behaviors in an online science learning environmentin school vs. at home -and explored the existence of some behavioral differences in terms of age and gender. They found that students who learned at home tended to spend more time learning but at a slower pace.…”
Section: Purpose Of the Study And Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the papers in the review (Ben-Zadok et al, 2010, 2011Xie, 2013) showed that click-track data analysis suffers from the same problem when several variables are combined to separately explain a construct. These papers chose the approach of looking at correlations of these variables separately and show significant relationships.…”
Section: First Category: Click-track Data Without Systematic Models Omentioning
confidence: 99%